Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To evaluate the piecewise-defined function \( f(x) \) at \( x = -1 \), follow these steps:
1. Identify the correct piece for \( x = -1 \):
The function \( f(x) \) is defined as:
[tex]\[ f(x) = \left\{\begin{array}{ll} 5x - 1 & \text{if } x < -3 \\ -3x - 1 & \text{if } x \geq -3 \end{array}\right. \][/tex]
Since \( -1 \geq -3 \), we use the second piece of the function: \( f(x) = -3x - 1 \).
2. Substitute \( x = -1 \) into the selected piece:
Substitute \( x = -1 \) into \( f(x) = -3x - 1 \):
[tex]\[ f(-1) = -3(-1) - 1 \][/tex]
3. Simplify the expression:
[tex]\[ f(-1) = 3 - 1 = 2 \][/tex]
Therefore, the value of the function at [tex]\( x = -1 \)[/tex] is [tex]\( \boxed{2} \)[/tex].
1. Identify the correct piece for \( x = -1 \):
The function \( f(x) \) is defined as:
[tex]\[ f(x) = \left\{\begin{array}{ll} 5x - 1 & \text{if } x < -3 \\ -3x - 1 & \text{if } x \geq -3 \end{array}\right. \][/tex]
Since \( -1 \geq -3 \), we use the second piece of the function: \( f(x) = -3x - 1 \).
2. Substitute \( x = -1 \) into the selected piece:
Substitute \( x = -1 \) into \( f(x) = -3x - 1 \):
[tex]\[ f(-1) = -3(-1) - 1 \][/tex]
3. Simplify the expression:
[tex]\[ f(-1) = 3 - 1 = 2 \][/tex]
Therefore, the value of the function at [tex]\( x = -1 \)[/tex] is [tex]\( \boxed{2} \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.